Analysis of parents' sex education towards ABK children in SLB Lampung province - Romlah, Romlah; Muslim, A. Bukhari (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2024)
Background: This study analyzes the role of parents in providing sex education to children with special needs (CWSN) in Special Schools (SLB) in Lampung Province. The focus is on empowering CWSN with knowledge about personal boundaries and self-protection to prevent sexual abuse. Despite its significance, sex education in Indonesia faces challenges, including limited parental knowledge and societal stigma.Aim: The research aims to explore parental roles, strategies, and challenges in delivering sex education, providing recommendations for effective and inclusive approaches tailored to the needs of CWSN.Method: A qualitative approach with a descriptive design was employed. Data were collected through in-depth interviews, participant observation, and documentation from 15 parents of CWSN aged 6–12 years. Triangulation ensured data validity, and analysis followed Miles and Huberman’s model, focusing on data reduction, presentation, and conclusion drawing.Results: Parents typically begin sex education after children reach 10 years, focusing on topics like sexual abuse prevention, physical boundaries, and gender identity. Family discussions were the most common strategy, with visual aids used selectively. Challenges included cultural stigma, resource limitations, and lack of institutional support.Conclusion: To enhance sex education for CWSN, earlier introduction using age-appropriate methods is recommended. Collaboration among parents, educators, and policymakers, along with resources like training programs and educational media, is crucial. These efforts can foster holistic development and protection for CWSN in Indonesia